2023
DOI: 10.4269/ajtmh.22-0630
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Progression to Chronic Chagas Cardiomyopathy: A Systematic Review and Meta-Analysis

Abstract: Approximately one-third of people with chronic Trypanosoma cruzi infection develop Chagas cardiomyopathy, which carries a poor prognosis. Accurate prediction of which individuals will go on to develop Chagas cardiomyopathy remains elusive. We performed a systematic review of literature comparing characteristics of individuals with chronic Chagas disease with or without evidence of cardiomyopathy. Studies were not excluded on the basis of language or publication date. Our review yielded a total of 311 relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 179 publications
3
1
0
Order By: Relevance
“…In the analysis of risk factors and comorbidities, our study shows similar results to those registered in other studies of individuals with PMC. (Freitas Lidani et al, 2020;Cutshaw et al, 2023). Hypertension was observed in 69.5% of the patients in this study, a similar percentage to that found in the CONAREC XII registry (Perna et al, 2015;Assuncão et al, 2016), where 69.3% had heart failure.…”
Section: Discussionsupporting
confidence: 89%
“…In the analysis of risk factors and comorbidities, our study shows similar results to those registered in other studies of individuals with PMC. (Freitas Lidani et al, 2020;Cutshaw et al, 2023). Hypertension was observed in 69.5% of the patients in this study, a similar percentage to that found in the CONAREC XII registry (Perna et al, 2015;Assuncão et al, 2016), where 69.3% had heart failure.…”
Section: Discussionsupporting
confidence: 89%
“…52 This could be due to the use of different mouse and parasite strains, 52 but may also reflect the lack of improvements of functional and survival outcomes in late-stage patient treatment, 7 even in cases of parasitological cure, and the disconnect between parasite burden and symptomatic vs asymptomatic chronic infection. 57 Importantly, our urine results concur with analysis of cardiac tissue in an independent infection model, which likewise showed only minor and incomplete metabolic restoration and functional restoration 56 days postbenznidazole treatment, even with successful parasite elimination. 56 As such, our method could represent a quick and noninvasive method to identify compounds with superior efficacy to benznidazole though this will need to be validated in additional animal models.…”
Section: ■ Discussionsupporting
confidence: 82%
“…This contrasts with acute-stage benznidazole treatment, which restored the plasma and heart metabolome . This could be due to the use of different mouse and parasite strains, but may also reflect the lack of improvements of functional and survival outcomes in late-stage patient treatment, even in cases of parasitological cure, and the disconnect between parasite burden and symptomatic vs asymptomatic chronic infection . Importantly, our urine results concur with analysis of cardiac tissue in an independent infection model, which likewise showed only minor and incomplete metabolic restoration and functional restoration 56 days postbenznidazole treatment, even with successful parasite elimination .…”
Section: Discussionsupporting
confidence: 63%
“…This contrasts with acute-stage benznidazole treatment, which restored the plasma and heart metabolome 42 . This could be due to the use of different mouse and parasite strains 42 , but may also reflect the lack of improvements of clinical outcomes in late-stage patient treatment 7 and the disconnect between parasite burden and symptomatic vs asymptomatic chronic infection 46 . Importantly, our urine results concur with analysis of cardiac tissue in an independent infection model, which likewise showed only minor and incomplete metabolic restoration 56 days post-benznidazole treatment 47 .…”
Section: Discussionmentioning
confidence: 99%